Influence of simulated gastric juice on surface characteristics of CAD-CAM monolithic materials - Cruz, Marlon E.M. [UNESP]; Simões, Rafaela [UNESP]; Martins, Samira B. [UNESP]; Trindade, Flávia Z. [UNESP]; Dovigo, Lívia N. [UNESP]; Fonseca, Renata G. [UNESP] (Elsevier, 2020)
Statement of problem: How the surfaces of monolithic esthetic restorations behave in the presence of acidic substances is unclear. Purpose: The purpose of this in vitro study was to evaluate the effect of simulated gastric juice on roughness, morphology, microhardness, substance loss, and color change of computer-aided design and computer-aided manufacturing (CAD-CAM) monolithic materials. Material and methods: Disks from Lava Ultimate, VITA ENAMIC, IPS e.max CAD, and VITA SUPRINITY were analyzed for roughness, morphology, and microhardness by using a confocal microscope, scanning electron microscope (SEM), and Vickers hardness tester. Substance loss was determined by weighing the specimens on an analytical balance, and color change (ΔE) was assessed by using a spectrophotometer based on the CIELab parameters. All analyses were carried out before and after acid exposure. Results: Acid exposure significantly decreased the roughness, having a very high effect size on this property. The material was highly decisive in determining the microhardness, presenting the following order: VITA SUPRINITY>IPS e.max CAD>VITA ENAMIC>Lava Ultimate. The mass was not significantly affected by the acidic challenge. No significant difference in ΔE was found between Lava Ultimate and VITA ENAMIC and between IPS e.max CAD and VITA SUPRINITY. Lava Ultimate showed a higher ΔE than IPS e.max CAD and VITA SUPRINITY, whereas VITA ENAMIC exhibited higher ΔE only when compared with VITA SUPRINITY. All materials presented ΔE<1. Conclusions: The simulated gastric juice significantly influenced the roughness of all the evaluated materials and promoted a color change classified as clinically undetectable in all materials.